Socio-economic characteristics and perceptions of cattle keepers and constraints to cattle production in western Kenya - Amimo, Joshua O.; Thumbi, Samuel M.; Inyangala, B.A.O.; Jung'a, J.O.; Mosi, R.O. (2011)
A cross-sectional survey was done in two Districts in Western Kenya to determine the socio-economic characteristics and perceptions of the cattle types kept. This involved socio-economic profiles of households, herd structure, reasons for keeping specific types of cattle and production and marketing constraints together with desired policy interventions to address the constraints. A total of 210 farmers randomly selected were interviewed. The data was analysed using Statistical Analysis System program. The majority of farmers (84%) were males. The households surveyed had an average family size of 8 (± 4.7) members. The mean land holding was 7.8 acres, with 98% of them owning the land. Most of the farmers (64%) in the two districts were literate and were involved in farming (95%) as the primary livelihood. The majority (80%) of the households preferred keeping indigenous zebu cattle over the exotic cattle. The first three reasons for keeping zebu cattle were, in that order, work, especially ploughing (91%), milk (74%) and as a repository for wealth (32%), which accounted for about 62% of the respondents. Diseases (86%), inadequate and low quality feed (12%) and high cost of drugs (2%) were the major constraints to livestock productivity. The farmers also identified lack of market (48%), poor infrastructure (39%) and misuse by the middlemen traders (12%) as main marketing constraints. The survey showed that there is need for the effective implementation of policies on adequate financial aid and regulation of farm input prices to the farmers as well as improved livestock extension services to enhance the production of ruminant livestock.